Glymphatic system disruption as a mediator of brain trauma and chronic traumatic encephalopathy. (January 2018) - Sullan, Molly J.; Asken, Breton M.; Jaffee, Michael S.; DeKosky, Steven T.; Bauer, Russell M.
Graphical abstract: Highlights: A model of the mediating effect of disrupted sleep on GS functioning and CTE pathology is proposed. Sleep disruption affects the ability of the GS to clear metabolic waste. Protein waste accumulates in perivascular spaces in CTE, which is one pathway used by the GS. Chronic disruption of the GS following brain trauma may increase the risk for developing CTE-like pathology and clinical symptomatology. Abstract: Traumatic brain injury (TBI) is an increasingly important issue among veterans, athletes and the general public. Difficulties with sleep onset and maintenance are among the most commonly reported symptoms following injury, and sleep debt is associated with increased accumulation of beta amyloid (Aβ) and phosphorylated tau ( p -tau) in the interstitial space. Recent research into the glymphatic system, a lymphatic-like metabolic clearance mechanism in the central nervous system (CNS) which relies on cerebrospinal fluid (CSF), interstitial fluid (ISF), and astrocytic processes, shows that clearance is potentiated during sleep. This system is damaged in the acute phase following mTBI, in part due to re-localization of aquaporin-4 channels away from astrocytic end feet, resulting in reduced potential for waste removal. Long-term consequences of chronic dysfunction within this system in the context of repetitive brain trauma and insomnia have not been established, but potentially provide one link in the explanatory chain connecting repetitive TBI with later neurodegeneration. Current research has shown p -tau deposition in perivascular spaces and along interstitial pathways in chronic traumatic encephalopathy (CTE), pathways related to glymphatic flow; these are the main channels by which metabolic waste is cleared. This review addresses possible links between mTBI-related damage to glymphatic functioning and physiological changes found in CTE, and proposes a model for the mediating role of sleep disruption in increasing the risk for developing CTE-related pathology and subsequent clinical symptoms following repetitive brain trauma.